Modulation of Glomerular ECTO-ADPase Expression by Oestradiol - Faas, M M; Bakker, W W; Klok, P A; Baller, J F W; Schuiling, G A (Thrombosis and Haemostasis, 1997)
The effect of 17-β-oestradiol (0E2) upon the activity of the glomerular anti-thrombotic ecto-enzyme ADPase was studied in cyclic and ovariectomized (OVX) Wistar rats. On day 0 (i.e. at the time of ovariectomy or 11 days after ovariectomy) ratsreceived OE2-releasing Silastic implants or empty implants and were sacrificed on day 3,10 or 21. Cryostat kidney sections were histochemically stained for ecto-ADPase activity using enzyme-histochemistry and glomerular reaction product was quantitatively evaluated by computerized image analysis. Both the histological distribution of reaction product in each glomerulus, as reflectedby the relative glomerular area covered with reaction product, as well as enzyme activity, as reflected by staining intensity of thereaction product, were scored. The results show significantly decreased histological distribution after OVX; OVX, however, did not change enzyme activity. It further appeared that OE2 (partly) prevented the decrease of histological distribution in OVX rats, while the enzyme activity was significantly increased by exogenous OE2. In cyclic rats, OE2 did not change histological distribution, although OE2 significantly increased enzyme activity in these rats.It is concluded that glomerular ecto-ADPase expression in the rat kidney is influenced by one or more ovarian factor(s), a very likely candidate being oestradiol. These results may thus point to a dual action of OE2 upon haemostasis: In addition to the known enhancement of procoagulatory plasma factors by OE2, also anti-aggregatory effects may be stimulated by OE2 as reflected by upregulation of vessel wall associated ecto-ADPase activity.